Recurrent paratesticular giant liposarcoma: A case report and literature review - Hua, Runmiao; Zhao, Liwei; Xu, Li; Sun, Ji; Huang, Jiaguo; Hua, Qiyan (Frontiers in Surgery, 2023)
Background: Primary paratesticular liposarcoma is rarely diagnosed among urinary tumors. In this study, through the retrospective analysis of clinical data and literature review, a case of recurrent paratesticular liposarcoma with lymph node metastasis after radical resection has been reported to explore novel strategies for the diagnosis, treatment and prognosis of this rare disease. Case summary: The present case involved a patient who was misdiagnosed as a left inguinal hernia for the first time two years ago, but was later diagnosed as mixed liposarcoma by using postoperative pathology. Currently, he is readmitted to the hospital with a recurrence of the left scrotal mass for more than 1 year. Combined with the patient's past medical history, we performed radical resection of the left inguinal and scrotal tumors and lymphadenectomy of left femoral vein. The postoperative pathology indicated that well-differentiated liposarcoma was accompanied by mucinous liposarcoma (about 20%), and lymph node metastasis of left femoral vein both of which occurred at the same time. After the operation, we recommended the patient to receive further radiation therapy, but the patient and his family refused, hence we followed up the patient closely for a long time. During the recent follow-up, the patient reported no complaints of discomfort, and no recurrence of mass in the left scrotum and groin area. Conclusion: After conducting extensive review of literature, we conclude that radical resection remains the key to treat primary paratesticular liposarcoma, while the significance of the lymph node metastasis is still unclear. The potential effects of postoperative adjuvant therapy depends on the pathological type, and hence close follow-up observation is essential.